A full-scale electrical-thermal-fluidic coupling model for li-ion battery energy storage systems. (25th February 2021) - Cao, Wenjiong; Qiu, Yishu; Peng, Peng; Jiang, Fangming
Highlights: A multi-physics model for practical large-scale BESSs simulations is proposed. The model deals with the electrical-thermal-fluidic behaviors in practical BESSs. The simulated BESS is of 18, 240 40Ah Li-ion batteries (1 MW/2MWh capacity). The model is validated by the operation data of an in-service commercial BESS. Case study corroborates the effectiveness and capabilities of the model. Abstract: Nowadays, lithium-ion battery (LIB) technology provides one of the most important approaches for large-scale electricity storage. In this work, an electrical-thermal-fluidic coupled model is proposed for practical LIB-based energy storage systems (ESSs). The coupled model is established based on the equivalent circuit model (ECM) which describes electrical behavior of LIBs, the airflow turbulent model, and the "single domain of multiple sub-regions" thermal model. Currents and voltages of LIB cells, airflow velocity field and pressure field, and temperature distribution in the whole ESS, can be simulated by the developed full-scale model. Simulation results of a practical commercial LIB ESS (1 MW/2 MWh) in typical frequency regulation operation, including electrical-thermal characteristics represented by currents and heat generation rates of LIBs in the ESS, flow characteristics represented by airflow field and mass flow rate distribution, ambient temperature sensitivity analysis represented by temperature distributions of the ESS initially under 27℃ and 38℃ ambient respectively, are displayed and discussed, exhibiting the capability of the proposed model. The proposed model has been validated by comparing the simulated results with the actual measured data; the reasonably good agreement demonstrates the effectiveness of the proposed model. Therefore, the established model has the potential to provide a feasible and powerful approach or tool to perform multi-physics simulations of practical large-scale LIB ESSs for different functions, including but not limited to detailed temperature evaluations, cooling structure optimization, materials selection, and thermal-safety status evaluating and monitoring.